Puzzle of the Fifth Ventricle: Left Ventricular Dissection Post Myocardial Infarction Resulting into Formation of a Neo-cavity: A Case Report and Literature Review - Neupane, Rajib; Shield, Daniel; Adhikaree, Ajay (Nepalese Heart Journal, 2026)
Left ventricular dissection is an exceedingly rare and atypical mechanical complication of myocardial infarction with high mortality. It is considered a sub-acute phase of cardiac rupture, which has a subtle presentation and often remains undiagnosed. Presented here is a case report of a 54-year-old female who developed features of acute heart failure 1 month following an anteroseptal wall myocardial infarction and was later diagnosed to have left ventricular dissection on echocardiogram. This case highlights few facts on ventricular dissection, which has been sparsely reported or explained in literature.